Orthogonal design and numerical simulation of room and pillar configurations in fractured stopes - Wu, Ai-xiang; Huang, Ming-qing; Han, Bin; Wang, Yi-ming; Yu, Shao-feng; Miao, Xiu-xiu (Journal of Central South University, 2014)
Room and pillar sizes are key factors for safe mining and ore recovery in open-stope mining. To investigate the influence of room and pillar configurations on stope stability in highly fractured and weakened areas, an orthogonal design with two factors, three levels and nine runs was proposed, followed by three-dimensional numerical simulation using ANSYS and FLAC 3D . Results show that surface settlement after excavation is concentrically ringed, and increases with the decrease of pillar width and distances to stope gobs. In the meantime, the ore-control fault at the ore-rock boundary and the fractured argillaceous dolomite with intercalated slate at the hanging wall deteriorate the roof settlement. Additionally, stope stability is challenged due to pillar rheological yield and stress concentration, and both are induced by redistribution of stress and plastic zones after mining. Following an objective function and a constraint function, room and pillar configuration with widths of 14 m and 16 m, respectively, is presented as the optimization for improving the ore recovery rate while maintaining a safe working environment.